2020
DOI: 10.1063/5.0003042
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on transport of momenta and energy in micropolar fluid suspended with dusty, mono and hybrid nano-structures

Abstract: Computational fluid dynamics (CFD) tools are applied to model transportation activity in micropolar fluid suspension with density particles and mono and hybrid metallic nano-sized structures. Highly complex computational models obtained by CFD simulations are executed via the finite element method. Galerkin residuals are approximated by Galerkin approximations. The assembled nonlinear system is linearized and solved iteratively under reasonable computational tolerance. A notable impact of vortex viscosity is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Numerical solution of the model is acquired via shooting method. Kaneez et al 51 , 52 investigated the numerical solution of micropolar fluid including dusty, mono and hybrid nono-structures. Khan et al 53 demonstrated the upper convected Maxwell MHD micropolar fluid with the impact of Joule heating and thermal radiation utilizing a hyperbolic heat flux.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical solution of the model is acquired via shooting method. Kaneez et al 51 , 52 investigated the numerical solution of micropolar fluid including dusty, mono and hybrid nono-structures. Khan et al 53 demonstrated the upper convected Maxwell MHD micropolar fluid with the impact of Joule heating and thermal radiation utilizing a hyperbolic heat flux.…”
Section: Introductionmentioning
confidence: 99%
“…analysis is performed successfully by implementing FEM [35][36][37][38][39]. This work is organized in five sections.…”
Section: Introductionmentioning
confidence: 99%
“…Zahba 20 has studied the heat flow of these liquids in the enclosure with dual hot fins. Kaneez et al 21,22 explored the role of dust particles and hybrid-nano structures on the heat conduction phenomena. Reddy et al 23 analyzed the dusty-hybrid liquid on an extended sheet with the properties of CNTs.…”
Section: Introductionmentioning
confidence: 99%